2022
DOI: 10.1101/2022.08.05.502904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of the TnsB transposase-DNA complex of type V-K CRISPR-associated transposon

Abstract: CRISPR-associated transposons (CASTs) represent unique mobile genetic elements that co-opted CRISPR-Cas immune systems for RNA-guided DNA transposition. Type V-K CAST is composed by Cas12k, TniQ, TnsC and TnsB. Here, we present the 2.46 A cryoelectron microscopy structure of the Scytonema hofmannii CAST TnsB transposase in complex with the strand transfer DNA in a post-catalytic state. The shTnsB strand transfer complex maintains the intertwined architecture of the MuA phage transpososome. However, the buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
2
0
0
Order By: Relevance
“…We first determined the minimal transposon sequences needed for robust activity and validated the importance of each transposase binding site (TBS) found within both left and right ends. Interestingly, our data revealed a broad degree of tolerance to mutagenesis of individual TBSs, a feature corroborated by recent TnsB transposase-DNA structures that show interactions mainly with the DNA backbone rather than specific nucleobases (3739). The presence of multiple binding sites within each transposon end might allow for accumulative specificity and affinity, and likely play a role in regulating transposition frequency.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We first determined the minimal transposon sequences needed for robust activity and validated the importance of each transposase binding site (TBS) found within both left and right ends. Interestingly, our data revealed a broad degree of tolerance to mutagenesis of individual TBSs, a feature corroborated by recent TnsB transposase-DNA structures that show interactions mainly with the DNA backbone rather than specific nucleobases (3739). The presence of multiple binding sites within each transposon end might allow for accumulative specificity and affinity, and likely play a role in regulating transposition frequency.…”
Section: Discussionsupporting
confidence: 85%
“…This dataset revealed that individual TBS point mutations can affect efficiency, particularly for positions 1, 6-9, and 12-14, but are not critical for integration. This more lenient sequence requirement is in line with recently published cryo-EM structures of DNA-bound TnsB from Tn 7 and Type V-K CAST systems, which revealed that many protein-DNA interactions occur with the phosphodiester backbone rather than specific nucleobases (3739).…”
Section: Resultssupporting
confidence: 78%